Cancer incidence in immigrants by geographical area of origin: data from the Veneto Tumour Registry, Northeastern Italy - Ferroni, Eliana; Guzzinati, Stefano; Andreotti, Alessandra; Baracco, Susanna; Baracco, Maddalena; Bovo, Emanuela; Carpin, Eva; Dal Cin, Antonella; Greco, Alessandra; Fiore, Annarita; Memo, Laura; Monetti, Daniele; et al. (Frontiers in Oncology, 2024)
Objective We investigated whether there are differences in cancer incidence by geographical area of origin in North-eastern Italy. Methods We selected all incident cases recorded in the Veneto Tumour Registry in the period 2015-2019. Subjects were classified, based on the country of birth, in six geographical areas of origin (Italy, Highly Developed Countries-HDC, Eastern Europe, Asia, Africa, South-central America). Age-standardized incidence rates and incidence rate ratio (IRR) were calculated, for all cancer sites and for colorectal, liver, breast and cervical cancer separately. Results We recorded 159,486 all-site cancer cases; 5.2% cases occurred in subjects born outside Italy, the majority from High Migratory Pressure Countries (HMPC) (74.3%). Incidence rates were significantly lower in subjects born in HMPC in both sexes. Immigrants, in particular born in Asia and Africa, showed lower rates of all site cancer incidence. The lowest IRR for colorectal cancer was observed in males from South-Central America (IRR 0.19, 95%CI 0.09-0.44) and in females from Asia (IRR 0.32, 95%CI 0.18-0.70). The IRR of breast cancer appeared significantly lower than Italian natives in all female populations, except for those coming from HDC. Females from Eastern Europe showed a higher IRR for cervical cancer (IRR 2.02, 95%CI 1.57-2.61). Conclusion Cancer incidence was found lower in subjects born outside Italy, with differences in incidence patterns depending on geographical area of origin and the cancer type in question. Further studies, focused on the country of birth of the immigrant population, would help to identify specific risk factors influencing cancer incidence.